OS 28-03 SECRETORY CAPACITY OF PANCREATIC BETA CELLS IS ENHANCED 6 MONTHS AFTER RENAL DENERVATION IN TREATMENT RESISTANT HYPERTENSIVE PATIENTS - Ott, Christian; Kistner, Iris; Schmid, Axel; Friedrich, Stefanie; Ditting, Tilmann; Veelken, Roland; Mahfoud, Felix; Boehm, Michael; Uder, Michael; Schmieder, Roland (Journal of Hypertension, 2016)
Renal denervation (RDN) lowers blood pressure (BP) by interruption of sympathetic nerve activity. A high sympathetic tone increases not only BP but also decreases pancreatic beta cell insulin secretion. Hence, the objective of the study was to analyze whether RDN improves secretory capacity of beta cells.In 40 patients (7 diabetics, 19 prediabetics, 14 non diabetics) with treatment resistant hypertension (defined by office BP >= 140/90 mmHg and diagnosis confirmed with 24-h ambulatory BP >= 130/80 mmHg), insulin secretion was measured before and 6 months after RDN (Simplicity flex catheter, Medtronic) by glucagon test. At each time point blood was sampled prior to glucagon administration and 6 minutes after intravenous injection of 1 ml glucagon for measurement of C-peptide, insulin and proinsulin (by ELISA).In these 40 patients (mean age 58 ± 12 years, mean office BP 154 ± 22 mmHg / 89 ± 14 mmHg while on 5.2 ± 1.4 antihypertensive drugs) office systolic and diastolic BP was significantly reduced 6 months after RDN (both p < 0.01). Fasting plasma glucose and HbA1c level was significantly reduced 6 month after RDN (both p < 0.01). Six months after RDN, the increase of C-peptide concentration and insulin concentration after glucagon injection was significantly higher compared to before RDN (both p < 0.05).Thus, our data indicate an improved pancreatic beta cell function after RDN in patients with treatment resistant hypertension.
EVALuna2:14605